DNA extraction from lip cosmetics’ prints: A Review (Medico Legal Update, 2023)
Background: Persistent use of lip cosmetics makes them one of the most regular evidence in crime againstfemales, with this concern, plenteous work has been done to differentiate various types of lip cosmetics on basisof their composition. However, the forensic and DNA perspective regarding the same remains unexplored to ahuge extent.Study: We looked at the DNA implications of lip stains as well as several ways for extracting DNA from lipcosmetic prints in this work.Conclusion: We came to the conclusion that DNA profiles created from lip cosmetics imprints are extremelyvaluable in forensic examination for personal identification because they are regarded the most crucial type oftransmission traces and are equivalent to finger-marks.